Analisis Permintaan Tenaga Kerja Wanita Di Industri Tempe Dedek Tj. Mulia Dalam Peningkatan Pendapatan Keluarga (Mutiara: Multidiciplinary Scientifict Journal, 2023)
The aim of the study was to analyze the demand for female workers in the tempemaking industry in order to increase family income. The data used in this study are primary data obtained from research survey results and secondary data. The research population is the total amount in the tempe-making industry in Tj. Glorious. The results of the study show that the education variable has a positive and significant effect on wages has a positive and statistically significant effect on the demand for labor while the husband's own income variable has a partially significant effect where the high coefficient of the wage variable strengthens the relationship to the demand for labor. This finding differs in theory from the influence of existing wages on the demand for labor in the tempe industry. The suggestions put forward in this research are that the Medan City Government is expected to further empower women to play a bigger role in efforts to improve family welfare, especially in the tempe-making industry. with small industry entrepreneurs in skills training for workers and facilitating capital matters in the form of channeling capital and bookkeeping for entrepreneurs and being able to provide support to tempe industry entrepreneurs in terms of sales promotion so they can market their products not only on a regional scale but also penetrate national and even international markets.